Low-Dose of Intrapulmonary Pirfenidone Improves Human Transforming Growth Factorβ1-Driven Lung Fibrosis - Okano, Tomohito; Kobayashi, Tetsu; Yasuma, Taro; D’Alessandro-Gabazza, Corina N.; Toda, Masaaki; Fujimoto, Hajime; Nakahara, Hiroki; Okano, Yuko; Takeshita, Atsuro; Nishihama, Kota; Saiki, Haruko; Tomaru, Atsushi; et al. (Frontiers in Pharmacology, 2020)
Idiopathic pulmonary fibrosis is a chronic, progressive, and lethal lung disease of unknown etiology. Anti-fibrotic drugs including pirfenidone are currently used for the treatment of the disease. The oral administration of pirfenidone is an effective therapy as demonstrated by several clinical trials although in some patients it causes severe adverse events. We hypothesized that low-dose intrapulmonary delivery of pirfenidone is effective in human transforming growth factorβ1-driven pulmonary fibrosis. To demonstrate our hypothesis we compared the therapeutic efficacy of varying doses of pirfenidone administered by oral and intranasal routes in a human transforming growth factor-β1 transgenic mouse with established pulmonary fibrosis. Amelioration of lung cell infiltration, inflammatory and fibrotic cytokines, lung fibrosis score, and hydroxyproline content was similar in mice with human transforming growth factor-β1-mediated pulmonary fibrosis treated with low-dose of intranasal pirfenidone and high-dose of oral pirfenidone. This study showed that pirfenidone is a potent inhibitor of human transforming growth factor-β1-driven lung fibrosis and that intrapulmonary delivery of low-dose pirfenidone produces therapeutic responses equivalent to high-dose of oral pirfenidone.